2012
DOI: 10.1590/s0100-204x2012000600007
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de arroz com uso de reguladores de crescimento, em diferentes sistemas de cultivo

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de reguladores de crescimento sobre o estabelecimento inicial e o desempenho agronômico de cultivares de arroz irrigado, em diferentes sistemas de cultivo. O experimento foi conduzido em ambiente controlado e em campo, com as cultivares Irga 424 e Irga 425, e os produtos ácido giberélico, tiametoxam e Haf Plus. Em campo, os tratamentos foram testados nos sistemas de cultivo convencional e pré-germinado. Em ambiente controlado, as substâncias avaliadas prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(19 reference statements)
1
4
0
2
Order By: Relevance
“…In the corn crop, according to Dan et al (2010), significant reductions in vigor that were caused by Carbofuran in corn seeds were observed after treatment and storage for a period of 30 days. Grohs et al (2012), evaluating the first count of normal seedlings at 7 days after sowing, verified that the applications of Cruiser 350 FS were efficient in stimulating the germination of different rice cultivars. According to these same authors, thiamethoxam as well as gibberellic acid, promoted a stimulus germination that was already expected, because these substances act in different stages of the germinative process, stimulating mainly the activity of key enzymes involved.…”
Section: Introductionmentioning
confidence: 68%
“…In the corn crop, according to Dan et al (2010), significant reductions in vigor that were caused by Carbofuran in corn seeds were observed after treatment and storage for a period of 30 days. Grohs et al (2012), evaluating the first count of normal seedlings at 7 days after sowing, verified that the applications of Cruiser 350 FS were efficient in stimulating the germination of different rice cultivars. According to these same authors, thiamethoxam as well as gibberellic acid, promoted a stimulus germination that was already expected, because these substances act in different stages of the germinative process, stimulating mainly the activity of key enzymes involved.…”
Section: Introductionmentioning
confidence: 68%
“…Similarly, Avelar et al (2011) reported that soybean seeds stored for six months with no treatment exhibited higher performance in comparison to treated seeds. In experiment with rice seed treated with Thiamethoxam was observed stimulus the first count, cultivar IRGA 425 obtained higher percentage compared to the control (Grohs et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
“…In maize seeds subjected to phytosanitary treatment and stored for six months exhibited lower normal seedlings number, indicating a possible phytotoxic effect of the treatment (Pereira et al, 2005). Grohs et al (2012) observed that of rice seeds germination treated with thiamethoxam was 50% higher than the witness. In another study, it was observed that rice seeds treated with thiamethoxam presented accelerated germination (Clavijo, 2008).…”
Section: Resultsmentioning
confidence: 92%
“…In cv. Irga 425 rice seeds, thiamethoxam treatment resulted in an increased germination of up to 60% (GROHS et al, 2012 (MAPA, 2008). Thus, thiamethoxam use increased germination to a level that meets the standards established by the current legislation, except for U. brizantha cv.…”
Section: Resultsmentioning
confidence: 99%